Analisis Yuridis Tanggung Jawab Platform Marketplace terhadap Peredaran Barang Palsu di Indonesia - Lingga Bagus Prakoso; Aturkian Laia (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
The rapid growth of electronic commerce in Indonesia has increased the circulation of counterfeit goods on marketplace platforms, causing losses to consumers and trademark owners. This study analyzes the legal status of marketplace platforms, their liability, legal protection for consumers and trademark owners, and the effectiveness of existing regulations. The research employs a normative legal method using statutory, conceptual, and case approaches based on the Consumer Protection Law, the Trademark and Geographical Indications Law, the Electronic Information and Transactions Law, and Government Regulation Number 80 of 2019. The findings show that marketplace platforms act as intermediary service providers and electronic commerce operators with active legal obligations. The safe harbor principle does not apply when platforms knowingly fail to implement adequate notice-and-takedown measures. However, regulatory effectiveness remains limited due to weak duty of care standards, inadequate seller verification, and poor institutional coordination. Stronger regulations and harmonized consumer and trademark protection are therefore essential